A critical study on the need for conjugal visit for married female convicted prisoners in Malaysia, with special reference to the position of The United States of America / Nurul Nadia Mohd Izmir, Nur Izzaida Zamani and Nur Azhani Mohd Azizan - Mohd Izmir, Nurul Nadia; Zamani, Nur Izzaida; Mohd Azizan, Nur Azhani (2008)
This research would cover the need of conjugal visit for married female convicted prisoners in Malaysia. The reason for us to embark upon such research is due to the fact that there is no existing right on conjugal visit in Malaysia. Our research is an attempt to consider the need of such right to be implemented in Malaysia, in consideration of the lessons that we could learn from other countries such as the United States that has adopted conjugal visit for quite some time. In Malaysia, the rights of the convicted prisoners for their basic needs are governed in the Prison Ordinances of Malaysia and Lock-up Rules 1952 (POL) and the Prison Act 1995. However, the right to conjugal visit is not included in the statutes. A conjugal visit is a scheduled extended visit during which an inmate of a prison is permitted to spend several hours or days in private, usually with a legal spouse. Conjugal visit helps in the rehabilitation process of the prisoners. It can also be seen as a good tool in maintaining inmates' relationship with their respective spouses and families, but it should be noted that most of the inmates' marriages are already on the rocks when they enter into prison. At the same time, providing such visit would harm the purpose of prison that is, to punish the inmates. We believe that conjugal visit is not necessary to be provided for married female convicted prisoners in Malaysia even as a mere privilege, because the disadvantages outweigh its values. However, if conjugal visit were to be provided to such prisoners, the Malaysian Prison Department should use experiences from other countries such as the USA as guidance. However, Malaysian culture, custom and religion must be taken into consideration.